The Development Evaluation of Needs in Developing Learning Lessons in the Digital Era of The Student Teaching in Faculty of Education Ramkhamhaeng University: Mixed Method - Suwannapha, Sirimongkon (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: This research aims to investigate the current state and desired conditions for the development of digital learning management among pre-service teacher interns at the Faculty of Education, Ramkhamhaeng University. The objectives of the study are threefold: (1) to examine the existing conditions and the desired state for the development of digital learning management among pre-service teacher interns; (2) to assess the essential requirements for enhancing digital learning management among pre-service teacher interns; and (3) to propose strategies for the development of digital learning management for pre-service teacher interns at the Faculty of Education, Ramkhamhaeng University. Methodology: The research utilizes a mixed-methods approach, incorporating both quantitative and qualitative research methods. Data collection tools include questionnaires and interviews for assessing the necessary requirements for digital learning management development. Statistical analyses such as frequency distribution, percentages, mean values, standard deviations, PNIModified method, and content analysis are employed to analyze the gathered data. Results: This research found that (1) The study found that the overall current state is high (mean = 3.99, SD = 0.49). When examined by dimension, the highest average was observed in the area of innovative technology media and learning environment organization, rated at a high level. Following closely were curriculum and course content, rated at a high level, while the lowest average was in the student dimension, also rated at a high level. The desired state overall is also high (mean = 4.45, SD = 0.48). When analyzed by dimension, the highest average was in the curriculum and course content dimension, rated at the highest level. Following this, the innovative technology media and learning environment organization dimension were also rated at a high level. The lowest average was in the student dimension, rated at a high level. (2) The essential requirements for developing digital learning management among pre-service teacher interns were examined. The dimensions of students, teachers, assessment and learning outcome measurement, learning management design, curriculum and course content, and media, technology, innovation, and learning environment organization had PNI(Modified) values of 0.141, 0.121, 0.119, 0.118, 0.113, and 0.092, respectively. (3) The development strategies for digital learning management in the digital age included: (3.1) Enhancing student skills in accessing and using various media, technology innovations, secure communication, and keeping pace with digital society trends. (3.2) Adapting teaching methods by incorporating innovative technology media to make teaching more effective. (3.3) Evaluating learning outcomes using contemporary computer programs and applications, involving students in the learning process. (3.4) Designing learning management to foster analytical thinking, diverse skills, and experiences that align with the age and interests of learners. (3.5) Developing curriculum and course content in a modern, engaging, and responsive manner under societal changes. (3.6)Utilizing and incorporating a variety of innovative media, technologies, and learning environment organization to enhance learning processes and contribute to the success of learners. Conclusion: The study focuses on the effectiveness of key learning management aspects, such as media, technological innovations, and classroom organization. It emphasizes addressing issues related to student participation. Additionally, the study should be subject to improvement and development to enhance learning processes in the digital age. It supports learning management strategies for both students and educators, aiming to equip them with knowledge, digital skills, and innovative teaching approaches. Furthermore, curriculum development should align with adaptability to the changing educational environment and keep pace with the evolving digital landscape.